AB1343 Prevalence of autoimmune diseases in catalonia: a population based study using a public big data analytics (PADRIS). (12th June 2018) - Sisó-Almirall, A.; Kostov, B.; Martínez Carbonell, E.; Retamozo, S.; Flores-Chavez, A.; González-Martínez, S.; Brito-Zerón, P.; Dedéu Baraldés, A.; Benavent Àreu, J.; Ramos-Casals, M.
Abstract : Objectives: To analyse the prevalence of autoimmune diseases (ADs) in Catalonia by using a public big data program (Public Data Analysis for Health Research and Innovation Program, PADRIS) Methods: We used the health insurance database of the Catalan National Health Insurance (CNHI) which includes all catalan population registered as insured population in 2016. The sample included 7, 483, 761 inhabitants. ADs were identified according to the corresponding International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes. A total of 33 autoimmune diseases were analysed classified in 4 main categories: rheumatic, systemic, organ-specific and immunodeficiency/autoinflammatory. The prevalence of ADs was calculated as the number of ADs patients divided by the total CNHI beneficiaries in the same year (rate per 1 00 000 persons, 95% confidence intervals -CI-) Results: The overall prevalence of ADs was 1202 per 1 00 000 persons (95% CI 1, 194–1, 209); the prevalence was 1455 (95%CI 1, 443–1, 467) in women and 939 (95%CI 929–949) in men. ADs were classified as organ-specific (43%), systemic (33%), rheumatic (23%) and immunodeficiency/autoinflammatory (1%) autoimmune diseases. The ADs with the highest prevalence rates included psoriasis (282 cases per 100, 000, 95% CI 278–286), rheumatoid arthritis (RA) (178 cases per 100, 000, 95% CI 175–181), polymyalgia rheumatic (98 cases per 100, 000, 95% CI 96–101), spondyloarthropathies (92 cases per 100, 000, 95% CI 90–94), systemic lupus erythematosus (SLE) (68 cases per 100, 000, 95% CI 66–70) and Sjögren's syndrome (59 cases per 100, 000, 95% CI 57–61). In 26 (79%) of the 33 ADs, the female:male ratio was higher than 1; the highest ratios were reported for Sjögren's syndrome (10.5:1), primary biliary cholangitis (5.8:1), SLE (5.4:1), systemic sclerosis (3.4:1) and rheumatoid arthritis (2.6:1). An enhanced prevalence of ADs was reported in Southern regions (1225 cases per 1 00 000 persons in Barcelona/Tarragona regions -CI95% 1, 216–1, 233- vs 1075 cases per 1 00 000 persons in Girona/Lleida regions -CI95% 1, 056–1, 093-, p<0.001). Conclusions: Nearly 90 000 catalans are classified as having an autoimmune disease, representing a prevalence of 1.2% of the total catalan population, a rate which reaches 1.5% in women. The highest frequencies are reported for psoriasis (0.28%), rheumatoid arthritis (0.18%), polymyalgia rheumatica (0.10%), spondyloarthropathies (0.09%), lupus (0.07%) and Sjögren syndrome (0.06%). Disclosure of Interest: None declared